Clinical researchThe association of carotid intima media thickness with dysfunctional HDL in South Asians - Dodani, Sunita; Marion, Lucy; Sharma, Gyanendra; Reed, Guy L.; George, Varghese (Archives of Medical Science, 2008)
Introduction: Coronary artery disease (CAD) is the leading cause of death in the United States and its rates are increasing in South Asians. Screening and detection of CAD risk factors can help prevent future risk CAD by early treatment. The objective of the current study was to determine the association of sub-clinical CAD using carotid intima media thickness (IMT) as a surrogate marker of atherosclerosis and dysfunctional HDL assess by novel cell free assay test in South Asians. Material and methods: A small pilot study on South Asians between the ages of 40-65 years was conducted. Carotid IMT was performed and dysfunctional HDL was assessed by novel cell-free assay. Results: The prevalence of sub-clinical CAD using carotid IMT (³0.80 mm) as a surrogate marker for atherosclerosis was seen in 41.4% [95% confidence limits (CL), 0.2347-0.5933]. HDL inflammatory Index values of ³1.00 were seen in 14 subjects (50%), suggesting pro-inflammatory (dysfunctional) HDL with (95% CL, 0.8772-1.4333). On logistic regression analysis, IMT values ³0.80 mm was associated with HDL inflammatory index (p=0.02), even after adjusting for age (p=0.03). Conclusions: The results of this study can be useful to explore further the associations and causes of dysfunctional HDL in South Asians in larger prospective studies. Emphasis needs to be given not only to the HDL levels but also the functionality of HDL, especially those with CAD risk factors who are at higher risk of future CAD. Early detection and treatment of dysfunctional HDL may reduce future CAD risk.